2015
DOI: 10.1038/ncomms8271
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative folding of intrinsically disordered domains drives assembly of a strong elongated protein

Abstract: Bacteria exploit surface proteins to adhere to other bacteria, surfaces and host cells. Such proteins need to project away from the bacterial surface and resist significant mechanical forces. SasG is a protein that forms extended fibrils on the surface of Staphylococcus aureus and promotes host adherence and biofilm formation. Here we show that although monomeric and lacking covalent cross-links, SasG maintains a highly extended conformation in solution. This extension is mediated through obligate folding coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 70 publications
5
74
0
Order By: Relevance
“…Because SasG domains have no tryptophans, (un)folding was followed by monitoring intrinsic tyrosine fluorescence. We have shown that ureainduced equilibrium denaturation curves of E-G5 2 monitored by fluorescence coincide with those recorded by ellipticity at 235 nm (7) and domain-specific FRET probes (9), showing that equilibrium unfolding of the two-domain construct is fully cooperative: two-state with concerted disruption of both domains and secondary and tertiary structure with no accumulation of intermediates (Fig. 1C).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Because SasG domains have no tryptophans, (un)folding was followed by monitoring intrinsic tyrosine fluorescence. We have shown that ureainduced equilibrium denaturation curves of E-G5 2 monitored by fluorescence coincide with those recorded by ellipticity at 235 nm (7) and domain-specific FRET probes (9), showing that equilibrium unfolding of the two-domain construct is fully cooperative: two-state with concerted disruption of both domains and secondary and tertiary structure with no accumulation of intermediates (Fig. 1C).…”
Section: Resultssupporting
confidence: 57%
“…We had previously shown that disorder-mediated thermodynamic cooperativity allows SasG to adopt long, mechanically strong, rod-like structures (9). Now, we have shown how this disorder coupled with the remarkable stability of the interdomain interface can result in cooperative folding kinetics, with no populated intermediates, across long distances.…”
Section: Resultsmentioning
confidence: 83%
“…In addition, 235 HN crosspeaks were identified, which is very close to the expected number (238). The presence of crowded resonances in the center of the 1 H, 15 N TROSY-HSQC spectrum of Phafin2 is consistent with the presence of random coil regions in the protein as deduced from far-UV CD analysis. NMR spectra of Phafin2 at higher temperatures than 308C were also recorded, yielding loss of resonances, and aggregation and precipitation of the protein (data not shown).…”
Section: Nmr Studies Of Phafin2supporting
confidence: 81%
“…Figure 6 shows that the 1 H, 15 N TROSY-HSQC spectrum of Phafin2 yielded a single set of resonances, indicating that the protein was highly homogenous at 308C. In addition, 235 HN crosspeaks were identified, which is very close to the expected number (238).…”
Section: Nmr Studies Of Phafin2mentioning
confidence: 80%
See 1 more Smart Citation